2017
DOI: 10.1017/s002191181700002x
|View full text |Cite
|
Sign up to set email alerts
|

Pork-Barrel Politics and Electoral Reform: Explaining the Curious Differences in the Experiences of Thailand and Japan

Abstract: A comparison of recent Thai and Japanese politics presents a puzzle. Both nations undertook similar electoral reforms at about the same time, but the results have been dramatically different. Thai leaders are party-oriented and have shifted away from the pork-barrel politics of the past. Japanese leaders and members of parliament remain candidate-oriented and continue Japan's pork-barrel policies. We explain these divergent outcomes by analyzing the different causes of and politics surrounding the electoral re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The LDP has been in control of government since 1955, with the exception of 10 months between 1993 and 1994 and 3 years between 2009 and 2012. A voluminous literature documents the single-minded focus of LDP politicians on securing pork-barrel projects for their districts (Curtis, 1971; Ramseyer and Rosenbluth, 1993; Horiuchi and Saito, 2003; Hirano, 2006; Scheiner, 2006; Krauss and Pekkanen, 2010; Naoi, 2015; Christensen and Selway, 2017; McMichael, 2018; Catalinac et al ., 2019). One driver of this was the electoral system used to select Members of the HoR.…”
Section: Case Of Japanmentioning
confidence: 99%
“…The LDP has been in control of government since 1955, with the exception of 10 months between 1993 and 1994 and 3 years between 2009 and 2012. A voluminous literature documents the single-minded focus of LDP politicians on securing pork-barrel projects for their districts (Curtis, 1971; Ramseyer and Rosenbluth, 1993; Horiuchi and Saito, 2003; Hirano, 2006; Scheiner, 2006; Krauss and Pekkanen, 2010; Naoi, 2015; Christensen and Selway, 2017; McMichael, 2018; Catalinac et al ., 2019). One driver of this was the electoral system used to select Members of the HoR.…”
Section: Case Of Japanmentioning
confidence: 99%
“…A study examining the geographic distribution of votes also found that LDP politicians collected votes from a wider geographic area after 1994 (Hirano, 2006). On the contrary, Christensen and Selway (2017) concluded that LDP politicians “have continued their long history of particularistic policies and pork barrel politics” after reform (see also Bawn & Thies, 2003; Krauss & Pekkanen, 2010; McKean & Scheiner, 2000). These studies highlight the fact that the new system tolerates dual candidacy, which enables the LDP to make candidates who lost their SMDs compete to obtain a PR seat.…”
Section: Case Of Japanmentioning
confidence: 99%
“…Some studies hold that this freed LDP politicians from having to generate personal sources of appeal, of which pork is one, and pushed them to adopt a more efficient electoral strategy of running on party platforms comprised of positions on programmatic goods (Carey & Shugart, 1995; Catalinac, 2015; Cox, 1990; Estevez-Abe, 2008; Noble, 2010; Rosenbluth & Thies, 2010; Shinada, 2006). Others disagree and identify features of Japan’s new system such as dual candidacy and the “best-loser” provision, which encourage candidates to remain focused on pork (Christensen & Selway, 2017; Krauss & Pekkanen, 2010; McKean & Scheiner, 2000). We offer another reason why pork continues: The reform did not alter the ability of incumbents to discern the relative levels of support from municipalities and influence allocations to those municipalities.…”
Section: Introductionmentioning
confidence: 99%
“…Thai voters got a separate vote for the PR tier, thus parties' success for these 100 extra seats (a not insignificant number given that the largest parties in past elections barely passed that number) relied solely on national prominence and party branding. Thai parties thus decided to run their top officials on this upper tier (Christensen and Selway 2017). They did so partly because said officials would be guaranteed these seats without having to campaign in the more uncertain constituencies.…”
Section: T H E S U F F I C I E N T C O N D I T I O N C L a I M : R E mentioning
confidence: 99%